2017
DOI: 10.1039/c6ra27590g
|View full text |Cite
|
Sign up to set email alerts
|

Toward a uniform description of hydrogen bonds and halogen bonds: correlations of interaction energies with various geometric, electronic and topological parameters

Abstract: Correlations between interaction energies and various structural parameters were established to reveal the differences between hydrogen bonds and halogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 80 publications
2
25
1
Order By: Relevance
“…Correlations between the sum of the electron density (Σ ρ int ) at the BCP and the sum of the stabilization energy can be performed. This allows the partitioning of the atom ··· atom interaction energy, providing insights into the energetic contribution of each interaction (Figure ) . The types of atom ··· atom intramolecular interactions and QTAIM data are listed in the Supporting Information (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Correlations between the sum of the electron density (Σ ρ int ) at the BCP and the sum of the stabilization energy can be performed. This allows the partitioning of the atom ··· atom interaction energy, providing insights into the energetic contribution of each interaction (Figure ) . The types of atom ··· atom intramolecular interactions and QTAIM data are listed in the Supporting Information (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…An Atoms in Molecules analysis of the topology of the electron density of [Fe(ent) 3 ] 3− obtained from DFT calculations revealed (3, −1) N–H⋯O bond critical points with properties indicative of closed-shell donor-acceptor interactions (ρ = 0.049 au, ∇ 2 ρ = 0.12) (Figure 3). 53,54 …”
Section: Resultsmentioning
confidence: 99%
“…Strong halogen-bonded complexes were found to exhibit different linear correlations from weak halogenbonded and hydrogen-bonded systems [445]. Nevertheless, for the latter two types of system, a uniform regression equation can be constructed.…”
Section: The Importance In Drug Design Of Similar To Hb Bondsmentioning
confidence: 99%
“…The dependence of the BSSE-corrected interaction energy (ΔE cor ) on the interatomic distance (rA /N ) appeared to be nonlinear for both halogen-bonded and hydrogen-bonded systems; the relationship between ΔE cor and the difference between r A/N and the sum of the van der Waals radii (Δr A/N ) can be fitted to a combined quadratic regression equation. Furthermore, it has been demonstrated that the linear correlations between ΔE cor and r b (BCP) (the electron density at bond critical points in the A/N bond) and its Laplacian V 2 r b (BCP) can be used to provide a combined description of hydrogen bonds and halogen bonds [445].…”
Section: The Importance In Drug Design Of Similar To Hb Bondsmentioning
confidence: 99%
See 1 more Smart Citation